Assessing attention and impulsivity in the variable stimulus duration and variable intertrial interval rodent continuous performance test schedules using dopamine receptor antagonists in female C57BL/6JRj mice. - Klem, L.; Nielsen, M. M.; Gestsdóttir, S. B.; Frandsen, S. L.; Prichardt, S.; Andreasen, J. T. (Psychopharmacology, 2023)
Rationale: Dopaminergic dysfunction is implicated in disorders of impulsivity and inattention. The rodent continuous performance test (rCPT) has been used to quantify changes in attention and impulsivity. Objective: To examine the roles of dopamine receptors in attention and impulsivity behaviours measured in the rCPT variable stimulus duration (vSD) and the variable intertrial interval schedules (vITI) using DA receptor antagonists. Methods: Two cohorts of 35 and 36 female C57BL/6JRj mice were examined separately in the rCPT, vSD, and vITI schedules, respectively. Both cohorts received antagonists of the following receptors: D1/5 (SCH23390, SCH: 0.01, 0.02, 0.04 mg/kg) and D2/3 (raclopride, RAC 0.03, 0.10, 0.30 mg/kg) in consecutive balanced Latin square designs with flanking reference measurements. The antagonists were subsequently examined for effects on locomotor activity. Results: SCH showed similar effects in both schedules, and the effects were reference-dependent in the vITI schedule. SCH reduced responding, but improved response accuracy, impulsivity, discriminability, and locomotor activity. RAC showed mixed effects on responsivity, but improved accuracy and discriminability. The discriminability improvement was driven by an increase in hit rate in the vITI schedule and a reduction in false alarm rate in the vSD schedule. RAC also decreased locomotor activity. Conclusion: Both D1/5 and D2/3 receptor antagonism reduced responding, but the outcome on discriminability differed, stemming from individual effects on hit and false alarm rate, and the weight of omissions within the calculation. The effects of SCH and RAC suggest that endogenous DA increases responding and impulsivity, but reduces accuracy and shows mixed effects on discriminability.